2010
DOI: 10.1590/s0104-77602010000400001
|View full text |Cite
|
Sign up to set email alerts
|

Remoção de hemiceluloses da madeira por tratamento de lixiviação alcalina com NaOH

Abstract: ABSTRACT:The aim of this work was to assess the impact of hemicellulose extraction in eucalyptus wood, through alkaline leaching (NaOH) of wood chips, on the subsequent kraft process (with varying sulphidity) and the quality of the pulp. The chips were initially saturated with water and treated with a NaOH solution in a liquor to wood ratio of 6:1 m 3 /t. The reaction times (3, 8, 14 and 16 hours), temperatures (70, 84 and 90°C) and NaOH concentrations (60, 80, 90, 120 and 156g/L) were assessed in atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The residue of the bark sample from the first extraction (n-hexane) was subjected to the next extraction using fresh solvents (ethyl acetate, methanol, and hot water 100 ℃) with the same procedure, successively. Lastly, 1 % sodium hydroxide (NaOH) was used to remove all the remaining secondary metabolites as well as low-molecular-weight carbohydrates (Júnior et al 2010, ASTM D1109-84 2001.…”
Section: Bark Collection and Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…The residue of the bark sample from the first extraction (n-hexane) was subjected to the next extraction using fresh solvents (ethyl acetate, methanol, and hot water 100 ℃) with the same procedure, successively. Lastly, 1 % sodium hydroxide (NaOH) was used to remove all the remaining secondary metabolites as well as low-molecular-weight carbohydrates (Júnior et al 2010, ASTM D1109-84 2001.…”
Section: Bark Collection and Extractionmentioning
confidence: 99%
“…In addition, 1 % NaOH was used to remove extractives which still bound tightly to the cell wall i.e. hemicellulose, sugars, and polymeric condensed tannins with high degree of polymeration (Júnior et al 2010, Sakai 2001). The extractive content by each solvent after successive extraction are shown in Table 1.…”
Section: Extractive Content Color Measurements and Ph Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CAE has its disadvantages, and the most significant one is likely its efficiency, which strongly depends on the specific raw material. This pretreatment has been extensively studied for various applications, and it has been observed that the extraction of hemicelluloses is more efficient in herbaceous lignocellulosic materials than in wood [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%